PENGARUH PENGGUNAAN LKPD BERBASIS METODE PEMBELAJARAN ACCELERATED LEARNING TEKNIK MASTER TERHADAP PENCAPAIAN KOMPETENSI FISIKA PESERTA DIDIK KELAS XI SMAN 7 PADANG - Yuni Azmanita; Masril Masril; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2017)
The attainment of students’ competence in physics in school has not been optimal yet. This is caused by several factors such as the less varied learning method implemented by teacher in the learning process, the limited textbooks in schools which are only used during the lesson hours, and Worksheet Students (LKPD) who can not make the students actively involved in the learning process. An alternative solution to this problem is to apply Worksheet Students (LKPD) based on accelerated learning method and MASTER technique. The purpose of this study was to investigate the effect of using LKPD based on accelerated learning method and MASTER technique towards the students’ attainment in learning physics in class XI SMAN 7 Padang. The study was a quasi experimental research with Nonequivalen Control Group. Samples were taken by using purposive sampling technique. The researcher employed observation sheet as the instrument for assessing the competence of attitude, written test for assessing the level of knowledge and performance, and the scoring rubric for assessing the competence of skills. The types of analysis used were the chart analysis for the attitudes competence, the simple linear regression for the knowledge competence, and the combination of both for the competence of skills. Based on the results of data analysis, there were three results in this study. First, the average value obtained for the attitude competence generally increased over weeks. Second, the average value of the knowledge competence in the experimental class was 80.56. The regression analysis showed that 23,02% of the students’ knowledge competence was influenced by the use of LKPD MASTER learning model. Thirdly, the average value of students’ skills competence in experimental class generally increased in every assessment. The regression analysis showed that 62,87% of students’ skills competence was influenced by LKPD based on accelerated learning method and MASTER technique. Therefore, it could be concluded that LKPD MASTER learning model is capable of increasing the students’ competence in physics in class XI SMAN 7 Padang